Acacetin attenuates Streptococcus suis virulence by simultaneously targeting suilysin and inflammation. (January 2022) - Xie, Shengnan; Zhang, Yan; Xu, Lei; Li, Shufang; Shen, Xue; Li, Li; Deng, Xuming; Zhou, Yonglin
Abstract: Streptococcus suis ( S. suis ), an important zoonotic pathogenic bacterium, can cause multiple diseases and fatal infections in both humans and animals. The emergence of highly virulent and extensively drug-resistant strains of S. suis has raised questions about the efficacy of available therapeutic agents, thereby necessitating novel therapeutic strategies. Suilysin (SLY) is one of the most essential determinants of virulence for the pathogenicity of S. suis capsular type 2 (SS2). In addition, inhibiting the excessive inflammatory response is a strategy to reduce the damage caused by SS2 infection. In this study, we identified acacetin as an effective inhibitor of SLY, which inhibited the oligomerisation of SLY without affecting bacterial growth. Furthermore, the addition of 4–16 μg/ml acacetin to the co-infection system of the cells reduced S. suis -induced inflammation by downregulating the activation of the MAPK signalling pathway, thereby alleviating the S. suis -mediated cell injury. Thus, in addition to the conventional antibiotic therapy, acacetin represent a potential drug candidate and strategy for the treatment of S. suis infections as it simultaneously inhibited the haemolytic activity of SLY and downregulated the inflammatory response. Highlights: In this study, it was found that acacetin as an effective inhibitor of SLY, which inhibited the oligomerisation of SLY without affecting bacterial growth. S. suis  induced inflammation response was reduced by downregulating the activation of the MAPK signaling pathway. Acacetin treatment significantly alleviated SLY-mediated cell injury. And such strategy, differing from antibiotics, further provides the basis for drug discovery against bacterial infection.